Climate Services and Communication for Development: The Role of Early Career Researchers in Advancing the Debate. Issue 5 (4th July 2019) - Donkor, Felix Kwabena; Howarth, Candice; Ebhuoma, Eromose; Daly, Meaghan; Vaughan, Catherine; Pretorius, Lulu; Mambo, Julia; MacLeod, Dave; Kythreotis, Andrew; Jones, Lindsey; Grainger, Sam; Golding, Nicola; et al.
ABSTRACT: Climate services entail providing timely and tailored climate information to end-users in order to facilitate and improve decision-making processes. Climate services are instrumental in socio-economic development and benefit substantially from interdisciplinary collaborations, particularly when including Early Career Researchers (ECRs). This commentary critically discusses deliberations from an interdisciplinary workshop involving ECRs from the United Kingdom and South Africa in 2017, to discuss issues in climate adaptation and climate services development in water resources, food security and agriculture. Outcomes from the discussions revolved around key issues somewhat marginalized within the broader climate service discourse. This commentary discusses what constitutes "effective" communication, framings (user framings, mental models, narratives, co-production) and ethical dimensions in developing climate services that can best serve end-users. It also reflects on how ECRs can help tackle these important thematic areas and advance the discourse on climate services.